Show y=tan(arcsin(x)) then y'=((1-x^2))^-3/2

Printable View

- Dec 10th 2012, 12:12 AMcamjensonDerivative proof
Show y=tan(arcsin(x)) then y'=((1-x^2))^-3/2

- Dec 10th 2012, 12:21 AMProve ItRe: Derivative proof
- Dec 10th 2012, 12:25 AMMarkFLRe: Derivative proof
I would rewrite the function first before differentiating. Draw a right triangle with opposite side x and hypotenuse 1 to represent an angle whose sine is x. Now, use the Pythagorean theorem to find the adjacent side, then take the tangent of this angle. What do you get?